2015
DOI: 10.5664/jcsm.4846
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trauma Type in the Risk for Insomnia

Abstract: Objective: Insomnia is common following exposure to trauma and can occur independently or as a feature of posttraumatic stress disorder (PTSD). However, there is limited research identifying risk factors associated with the development of insomnia following exposure to a traumatic event. The goal of this study was to evaluate the role of specifi c trauma types in the risk for insomnia in a community sample of urban African Americans young adults. Methods: A sample of 554 nonclinical, urban, young adult African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…PTSD was a significant mediator, with a large indirect effect accounting for over half (61%) of the total effect of interpersonal PTE exposure on disturbed sleep. This is consistent with additional results from Hall Brown and colleagues [14], who found that the odds ratios for interpersonal traumas predicting endorsement of moderate to severe insomnia significantly decreased following the inclusion of PTSD and nocturnal fears into the model. We also found that AUD symptoms were a significant mediator of the relationship between interpersonal PTE exposure and sleep, although the magnitude of the indirect effect was not as high as for PTSD: AUD symptoms accounted for ~17% of the total relationship.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…PTSD was a significant mediator, with a large indirect effect accounting for over half (61%) of the total effect of interpersonal PTE exposure on disturbed sleep. This is consistent with additional results from Hall Brown and colleagues [14], who found that the odds ratios for interpersonal traumas predicting endorsement of moderate to severe insomnia significantly decreased following the inclusion of PTSD and nocturnal fears into the model. We also found that AUD symptoms were a significant mediator of the relationship between interpersonal PTE exposure and sleep, although the magnitude of the indirect effect was not as high as for PTSD: AUD symptoms accounted for ~17% of the total relationship.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have examined sleep following specific traumatic events (e.g., hurricanes, earthquakes, combat), but few have looked at multiple trauma types within the same sample [14]. A recent study that examined various traumatic events in an urban young adult sample found that interpersonal traumas were potent predictors of insomnia [14], which, taken with our results, shows that findings across trauma and sleep are robust.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…One study found that specific trauma types (e.g., sexual trauma, physical assault, and witnessing sudden violent death) are linked with subsequent sleep disturbance severity [59]. Also, sleep disturbance may initiate or exacerbate PTSD.…”
Section: Rdoc Framework-based Correlates Of Trauma and Sleepmentioning
confidence: 99%